2020
DOI: 10.21203/rs.3.rs-54097/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-omics examination of Q fever fatigue syndrome identifies similarities with chronic fatigue syndrome

Abstract: Background: Q fever fatigue syndrome (QFS) is characterised by a state of prolonged fatigue that is seen in 20% of acute Q fever infections and has major health-related consequences. The molecular mechanisms underlying QFS are largely unclear. In order to better understand its pathogenesis, we applied a multi-omics approach to study the patterns of the gut microbiome, blood metabolome, and inflammatory proteome of QFS patients, and compared these with those of chronic fatigue syndrome (CFS) patients and health… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…QFS is characterized by a state of prolonged fatigue and has major health‐related consequences, including long‐term psychosocial impairment (Reukers et al., 2019). Recent results highlighted the striking resemblance of the gut microbiome from QFS patients with chronic fatigue syndrome patients due to other causes (Raijmakers et al., 2020). Due to the lack of acute pathognomonic symptoms, human cases are likely to be underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…QFS is characterized by a state of prolonged fatigue and has major health‐related consequences, including long‐term psychosocial impairment (Reukers et al., 2019). Recent results highlighted the striking resemblance of the gut microbiome from QFS patients with chronic fatigue syndrome patients due to other causes (Raijmakers et al., 2020). Due to the lack of acute pathognomonic symptoms, human cases are likely to be underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the relative abundance of Actinobacteria in the gut was significantly lower in Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) patients than the healthy controls 44 . In addition, a decrease in Actinobacteria when comparing Q fever fatigue syndrome (QFS) patients to healthy controls (HCs) was also observed 45 . In this study, the abundance of Actinobacteria was decreased after exhaustive swimming, which could be reversed after ACJ treatment.…”
Section: Discussionmentioning
confidence: 52%
“…44 In addition, a decrease in Actinobacteria when comparing Q fever fatigue syndrome (QFS) patients to healthy controls (HCs) was also observed. 45 In this study, the abundance of Actinobacteria was decreased after exhaustive swimming, which could be reversed after ACJ treatment.…”
Section: Alterations Of the Intestinal Microbiota Abundancementioning
confidence: 48%
“…(2015) showed in their work that cognitive‐behavioural variables may also play a role in that there is a negative association between physical activity and CFS after Q fever infection. The bacterial strain additionally appears to play a decisive role (Sukocheva et al., 2010; Raijmakers et al., 2020). In summary, CFS is a highly complex clinical picture with a heterogeneous pattern of influencing factors.…”
Section: Discussionmentioning
confidence: 99%